STRATEGI PENINGKATAN PARTISIPASI MASYARAKAT DALAM PERENCANAAN SUSTAINABLE DEVELOPMENT GOALS (SDGs) DESA. STUDI KASUS: DESA CIBURIAL, KECAMATAN CIMENYAN, KABUPATEN BANDUNG, JAWA BARAT - RIke Anggun Artisa (Inovasi Pembangunan : Jurnal Kelitbangan, 2023)
Village Sustainable Development Goals (SDGs) program to realize the acceleration of achieving sustainable development goals. The Village SDGs in Ciburial Village have been implemented in 2021 and 2022 Ciburial Village will re-implement the Village SDGs program, but in practice, there are still the same problems, namely the lack of community participation in the program. This study aims to determine the level of community participation in the Village SDGs and formulate appropriate strategies to increase community participation so that the implementation of the Village SDGs can run optimally. The method used in this research is descriptive qualitative by taking data through interviews, observation, and documentation. In formulating a strategy to increase community participation in the implementation of the Village SDGs, a SWOT analysis will be used, this SWOT analysis will describe internal and external conditions regarding existing strengths, weaknesses, opportunities, and threats to determine strategies that can make village communities play an active role in the Village SDGs that will be implemented. run by the Ciburial Village Government.